Follow-Up of Newborns with Neural Tube Defects: A Single Center Experience - Tandircioglu, Umit Ayse; Ensert Cihan, Cansu Kethuda; Celik, Hasan Tolga; Bilginer, Burcak; Yigit, Sule (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVES: Neural tube defects, defined as the developmental malformations of the central nervous system, are seen in our country at a rate of three per thousand on average. Our study aims to retrospectively evaluate patients with neural tube defects hospitalized in our intensive care unit for the last decade. STUDY DESIGN: Demographic data, prenatal-maternal characteristics, surgical operation time, intensive care follow-up, and long-term neurological-developmental results of these patients were also evaluated. RESULTS: Eighty-six percent (n=31) of the patients were diagnosed prenatally. Arnold Chiari type 2 and type 3 malformation was 64% (n=23) and 3% (n=1), respectively. Eighty-nine (n=32) percent of these patients had meningomyelocele, whereas 90% (n=27) of them had defects in the lumbosacral region. The patients were operated on the median postnatal 9th day (4-27). Compared patients who were operated on in the 1st week to the patients operated on following the first week, any difference was not detected in terms of neuromotor and cognitive development, and urinary/stool incontinence frequency. Of 28 patients whose long-term follow-up was questioned, 7 (25%), 25 (89%), and 16 (57%) were able to walk, talk, and go to school along with being compatible with their peers, respectively. CONCLUSION: We presented our center’s experience to make a significant contribution to the decrease of the neural tube defect frequency, which is commonly seen in our country compared to developed countries.